Finite Element Modeling for Flexible Pavement Behavior under Repeated Axle Load - Aljaleel, Zainab M.; Yasoub, Nahla; Atemim, Yahya K. H. (Engineering, Technology & Applied Science Research, 2024)
Accurate assessment of flexible pavement behavior requires a computational model that is able to predict the permanent deformation of the pavement under heavy load and its response with different thicknesses. This study developed several realistic models using advanced Finite Element Analysis (FEA) techniques employing the ABAQUS/CAE finite element program. The model integrates measured tire pavement contact stresses, moving wheel loads, and the viscoelastic properties of the asphalt layer. The model undergoes fine-tuning through the utilization of implicit dynamic analysis and variance in thickness. The simulations demonstrate that the viscoelastic behavior is more susceptible to changes in thickness. Furthermore, variation in thicknesses showed different pavement and rut depth behavior. The thinner the thickness is, the less resistance is applied to loading pressure and when the number of load repetitions increases, the depth of the rut also increases, leading to permanent deformation and consolidation with each passage of a heavy vehicle.